RUPTURE OF ABDOMINAL AORTIC ANEURYSM IN RENAL TRANSPLANT PATIENT - B. V. Fadin; I. G. Lesсhenko; V. V. Rzhannikov; V. V. Andreev; A. V. Gasnikov; A. A. Gasnikov; A. V. Kostenetskiy; I. V. Sablin (Вестник трансплантологии и искусственных органов)
The purpose of this article was to report our first experience in surgical treatment of aortic aneurism rupture in patient of 55 years old with renal transplant. Aortic aneurism rupture always associated with high mortality, and urgent operative procedure is also rather complicative and has also in bad anatomical conditions. The expectation of good collateral circulation for renal transplant, quick cross-clamp time and easy graft replacement may not always be the case. We believe that trans- planted kidney should be protected when ever feasible, especially in urgent procedure.